Mitologi Dalam Video Game: Pesan-pesan Politik Dalam Video Games Amerika Serikat - Fanani, Fajriannoor (Jurnal The Messenger, 2011)
Video Game, especially in Indonesia, has been long seeing as kid toy with minimum or no psychological impact to the player. This view is a serious mistake since video game able to transmit violence message to political message into their audience or player. Political message especially is very omnipresent in such game as Red Alert, Generals and others FPS or RTS games. The message on these games is higly political and contains political views the developer has. This writing tries to read the political messages on games like Red Alert and Counter Strike to find myth the developer create or believe and search out why these myths is present. Barthes analysis on semiotics were used to read not only the denotative meaning of the message, but also find the connotative message and finaly find the myths wrapped around the games.